South African Life Sciences teachers’ pedagogical beliefs and their influence on information communication and technology integration - Ramnarain, Umesh; Ncube, Rumbidzai; Teo, Timothy (Frontiers in Education, 2023)
Evidence suggests that learners actively construct knowledge and improve digital literacy when Information Communication and Technologies (ICTs) are used effectively. However, ICTs have not been exploited adequately in a science classroom. Early research argues that teachers’ pedagogical beliefs are potential barriers to delaying effective ICT integration in teaching and learning. In South Africa, research is silent regarding investigating Life Sciences teachers’ pedagogical beliefs translating into ICT integration. Hence, this study intended to close the knowledge gap and add to the body of knowledge. This study adopted a qualitative design to investigate three South African Life Sciences teachers pedagogical beliefs in Gauteng province. Qualitative data were collected from three Life Sciences teachers through lesson observations and semi-structured interviews. Teachers were observed teaching grade 11 Life Sciences classes. The video recordings were analyzed using the Teaching Dimension Observation Protocol (TDOP) to confirm findings from the questionnaire and establish how teachers integrate technology into teaching. Lastly, interviews were conducted to triangulate findings from lesson observations and questionnaires. The teachers integrated technology in ways that supported traditional beliefs. The results indicate the complexity of the relationship between pedagogical beliefs and ICT integration in practice. Teachers reflected on challenges in ICT integration that possibly impacted on their practices of ICT integration. They referred to a lack of learner access to smart devices and issues surrounding WiFi connectivity. In addition, teachers suggested that they needed training on innovative practices in ICT integration.